2017
DOI: 10.2147/ijn.s146875
|View full text |Cite|
|
Sign up to set email alerts
|

Cooperation of IRAK1/4 inhibitor and ABT-737 in nanoparticles for synergistic therapy of T cell acute lymphoblastic leukemia

Abstract: T cell acute lymphoblastic leukemia (T-ALL) is caused by clonal expansion of variant T cell progenitors and is considered as a high risk leukemia. Contemporary single chemotherapy has a limited effect due to dynamic and versatile properties of T-ALL. Here IRAK1/4 inhibitor and ABT-737 were co-encapsulated into polyethylene glycol modified poly (lactic-co-glycolic acid) nanoparticles (IRAK/ABT-NP) to enhance synergistic therapy of T-ALL. The formulation was optimized to achieve high drug loading using Box-Behnk… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
25
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(25 citation statements)
references
References 35 publications
0
25
0
Order By: Relevance
“…To generate the human cell line xenograft in ALL mouse model, we injected Jurkat cells (1 × 10 6 cells) into the tail veins of the female NPG mice. 28 After 7 days, we randomly placed the mice in three groups. Over the course of 2 weeks, 6-MPNs and 6-MPCs were administered at 20 mg/kg once daily by oral gavage (n = 6), and PBS was administered as the control.…”
Section: Methodsmentioning
confidence: 99%
“…To generate the human cell line xenograft in ALL mouse model, we injected Jurkat cells (1 × 10 6 cells) into the tail veins of the female NPG mice. 28 After 7 days, we randomly placed the mice in three groups. Over the course of 2 weeks, 6-MPNs and 6-MPCs were administered at 20 mg/kg once daily by oral gavage (n = 6), and PBS was administered as the control.…”
Section: Methodsmentioning
confidence: 99%
“…Most reports focus on drug delivery to the T cell surface, thus not requiring nanoparticle internalization. 14,[167][168][169]171 Although this is a valuable approach for drugs that can be delivered to the cell surface, in this review, we focus on strategies for nanoparticle-mediated intracellular drug delivery to T cells, noting that most reported studies originate from the field of oncology 19,26,140,144,[172][173][174][175][176][177] and HIV. [178][179][180][181][182][183] For a detailed listing of the studies described in this section, see Table 2.…”
Section: Nanoparticle-mediated Drug Delivery To T Cells: Successes To...mentioning
confidence: 99%
“…Despite the importance of T cells in various diseases, there are relatively few studies exploring direct T cell-targeted drug delivery using nanoparticles. Most reports focus on drug delivery to the T cell surface, thus not requiring nanoparticle internalization. , , Although this is a valuable approach for drugs that can be delivered to the cell surface, in this review, we focus on strategies for nanoparticle-mediated intracellular drug delivery to T cells, noting that most reported studies originate from the field of oncology ,,,, and HIV. For a detailed listing of the studies described in this section, see Table .…”
Section: Nanoparticle-mediated Drug Delivery To T Cells: Successes To...mentioning
confidence: 99%
See 1 more Smart Citation
“…To improve the solubility and bioavailability of ABT-737, two different research teams have encapsulated the drug in nanoparticles (NPs). , Schmid et al . showed that encapsulating ABT-737 in PEGylated polymeric NPs could reduce the thrombocytopenia associated with delivery of the free drug .…”
mentioning
confidence: 99%